The Underpinning of Technical Training of Talented male Football athletes From 11 To 12 Years Old After A Training Year - Dr. Pham Thi Le Hang*,Dr. Nguyen Thi Gam (Innovative Journal of Medical and Health Sciences, 2019)
The aim of this was to underpin technical training in football players 11-12 years old. For improving technical skills in football players, sixty three talented male Vietnam football players 11-12 years old have participated in this quasi-experimental study. After modifying the complex of technical tests by our research group, the technical training was underpinned due to their mistakes in technical skills. The quality and quantity of techniques were improved after designed technical training in this age.